ChemInform Abstract: Rhodium(I)‐Catalyzed Cycloisomerization of Benzylallene‐Alkynes Through C—H Activation. Issue 1 (January 2015) - Kawaguchi, Yasuaki; Yasuda, Shigeo; Kaneko, Akira; Oura, Yuki; Mukai, Chisato
Abstract A novel Rh‐catalyzed cycloisomerization of a variety of benzylallene‐alkyne substrates giving tricyclic products in moderate to good yields is presented.